2018
DOI: 10.1074/jbc.ra118.002933
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock promotes inclusion body formation of mutant huntingtin (mHtt) and alleviates mHtt-induced transcription factor dysfunction

Abstract: PolyQ-expanded huntingtin (mHtt) variants form aggregates, termed inclusion bodies (IBs), in individuals with and models of Huntington's disease (HD). The role of IB diffusible mHtt in neurotoxicity remains unclear. Using a ponasterone (PA)-inducible cell model of HD, here we evaluated the effects of heat shock on the appearance and functional outcome of Htt103Q-EGFP expression. Quantitative image analysis indicated that 80-90% of this mHtt protein initially appears as "diffuse" signals in the cytosol, with IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 84 publications
2
46
0
Order By: Relevance
“…Co-immunoprecipitation results showed that ZnT3 protein was not detected in aggregates, suggesting that down-regulation of ZnT3 does not come from the recruit of mHtt. Additionally, mHtt affects gene expression via altering the activity of transcription factors or abnormally interacting with ones [74][75][76]. Two major transcriptional pathways, namely CRE and Sp1mediated transcription, have been extensively studies in HD [53].…”
Section: Discussionmentioning
confidence: 99%
“…Co-immunoprecipitation results showed that ZnT3 protein was not detected in aggregates, suggesting that down-regulation of ZnT3 does not come from the recruit of mHtt. Additionally, mHtt affects gene expression via altering the activity of transcription factors or abnormally interacting with ones [74][75][76]. Two major transcriptional pathways, namely CRE and Sp1mediated transcription, have been extensively studies in HD [53].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of HSP90 by chemical inhibitor or knockdown leads to degradation of mHtt and mAtax-3. Heat shock and HSP70 are known to enhance mHtt aggregation and provide cytoprotection (42). Sorbitol, a chemical chaperone has been shown to promote mHtt aggregation and reduce cytotoxicity of mHtt.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular chaperones of HSP family (HSC70, HSP70, HSP90) are known to affect mutant protein aggregation. HSC70 has been shown to suppress protein aggregation whereas HSP70 and heat shock are reported to enhance protein aggregation (38)(39)(40)42). We hypothesized that OPTN may be promoting aggregation of mutant proteins by modulating the function of HSP70 family chaperones.…”
Section: How Does Optineurin Promote Mutant Protein Aggregation?mentioning
confidence: 97%
See 1 more Smart Citation
“…The effects of transient heat shock in driving mHtt IB formation is dependent on the production of HSP chaperones 9 , proteins widely acknowledged to play important roles in protein folding, structuring, and quality control 11,12 . Here, we used osmolytes as tools to further assess the role of protein structuring in driving the assembly and aggregation of the intrinsically disordered polyQ-Htt exon1 protein into IBs.…”
mentioning
confidence: 99%